VARIATION IN BIOFUEL POTENTIAL OF TWELVE CALOPYLLUM INOPHYLLUM POPULATIONS IN INDONESIA - Budi Leksono; Rina Laksmi Hendrati; Eritrina Windyarini; Trimaria Hasnah (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2014)
The global energy crisis has raises demand for biofuel prices. It has driven the world to enhance environmentally-friendly renewable-energy (biofuel) production. Oil from the seeds of Calophyllum inophyllum (nyamplung) which can be harvested up to 50 years, is one of such potential biofuel source. Methods for biofuel production from nyamplung seeds have been developed at an industrial scale by cooperative in Cilacap (Java) and Energy Self-Sufficient Villages (Desa Mandiri Energi) in Banyuwangi, Purworejo, Kebumen, Ujung Kulon (Java) and Selayar (South Sulawesi). However, there is only a limited-information available on biofuel potential, in term of productivity and quality, from nyamplung populations. This paper reports the variations in biofuel potential among 12 populations in Indonesia (6 from Java, 6 outside Java). The oil was extracted using a combination of vertical hot press (VHP) and screw press expeller (SPE) methods, followed by degumming to make refined oil, and esterification-transesterification to turn it into biodiesel. The result show great variation of biofuel content among the population. Oil production percentage varies from 37-48.5% (VHP) and 50-58% (SPE) crude oil, 36-48% (VHP) and 40-53% (SPE) refined oil, and 1733% (SPE) for biodiesel. Seed resin content is responsible for most of the variation after degumming. DNA analysis shows genetic variation among populations ranges from intermediate within Java to high ouside Java and is intermediate within populations. Information about biofuel content and potential of populations and genetic variation between and within population are important factors for establishment of geneticallyimproved seed-sources for biofuel production from nyamplung.